AEC Glacier alpine bluegrass - Darroch, B. A.; Acharya, S. N.; Woosaree, J. (Canadian Journal of Plant Science, 2002)
AEC Glacier alpine bluegrass, Poa alpina L., is a reclamation cultivar developed for use in reclaiming and revegetating disturbed sites at high elevations. It is the second alpine bluegrass cultivar released by the Alberta Environmental Centre, Vegreville, AB. This cultivar is expected to complement a prior release, AEC Blueridge alpine bluegrass. AEC Glacier is adapted to high elevations where it is capable of rapid growth and seed production. Key words: Alpine bluegrass, Poa alpina, cultivar description, reclamation